Implementasi Blocking Situs Di Router Mikrotik RB 2011 Dengan Menggunakan Web Proxi Studi Kasus STIE-Musi Rawas Lubuklinggau - Armanto Armanto (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2017)
Implementation Bolocking proxy router Rb site in 2011 With Using a proxy web stie-Musi Rawas In Lubuk Linggau.on currently stie Musi Rawas network is not equipped with adequate security firewaal so that today many abuses of the Internet that led to such negative, his banayak Site not filtered by a network system in stie-musi Rawas Lubuklinggau so many who misuse the internet as open sites that are prohibited opened or negative sites. With the blocking of these sites students or educators and education personnel could not open negative sites anymore, because the site is already terblikir by using proxy os designed to block sites that are considered negtive and dilekapai with a feature of the router is very effective for blocking sites and network security. In this study, using several tools to support this study as one unit mikrotik router rb 2011 which is used mainly as a network server, one laptop for performing settings on the router, one fruit swich to the distribution network per computer and 2 wireless to the spread of the Internet network through signal wireles or a wireless internet connection and an internet connection in the can from Indonesian telecoms. Keywords: Block sites using webproxy Mikrotik